Interspecific introgression mediates adaptation to whole genome duplication - Marburger, Sarah; Monnahan, Patrick; Seear, Paul J; Martin, Simon H; Koch, Jordan; Paajanen, Pirita; Bohutínská, Magdalena; Higgins, James D; Schmickl, Roswitha; Yant, Levi (Nature communications, 2019)
Adaptive gene flow is a consequential phenomenon across all kingdoms. Although recognition is increasing, there is no study showing that bidirectional gene flow mediates adaptation at loci that manage core processes. We previously discovered concerted molecular changes among interacting members of the meiotic machinery controlling crossover number upon adaptation to whole-genome duplication (WGD) in Arabidopsis arenosa. Here we conduct a population genomic study to test the hypothesis that adaptation to WGD has been mediated by adaptive gene flow between A. arenosa and A. lyrata. We find that A. lyrata underwent WGD more recently than A. arenosa, suggesting that pre-adapted alleles have rescued nascent A. lyrata, but we also detect gene flow in the opposite direction at functionally interacting loci under the most extreme levels of selection. These data indicate that bidirectional gene flow allowed for survival after WGD, and that the merger of these species is greater than the sum of their parts.
Keywords: Gene Duplication; fyziologická adaptace; meióza; ploidie; rostlinné geny; Genes, Plant; druhová specificita; Genome, Plant; Adaptation, Physiological; Meiosis; duplikace genu; Species Specificity; genom rostlinný; Polymorphism, Genetic; polymorfismus genetický; Ploidies; Arabidopsis